Evaluation of minimally invasive plate osteosynthesis of distal femoral fracture by mini-open technique with femoral distractor and traction table: a prospective review of 26 cases - Ghosh, Tapas Kumar; Banik, Rajeeb; Bhattacharjya, Bijoy (International Journal of Research in Orthopaedics, 2020)
Background: Different methods exist for fracture reduction and submuscular plating in distal femur intra-articular and metaphyseal extra-articular fractures. Apart from knee flexion, femoral distractor and traction table are commonly used for alignment of fractures in minimally invasive techniques. Methods: 26 distal femoral fractures (all closed fractures) were operated (14 cases in traction table, 12 cases in femoral distractor). Partial articular/unicondylar fractures were excluded from our study. Mean patient age was 42 years (range 18 to 60 years). Evaluation was done by knee society score (KSS). Results: Mean time of radiological union was 23.2 weeks (range 20-28 weeks). 23 fractures united uneventfully, one patient had wound infection, and 2 cases had non-union with implant failure. Debridement in infected implant and re-fixation with long plate and bone grafting were done for fracture union in these two cases. According to KSS, excellent outcome were seen in 6 patients, 10 had good, 8 had fair and 2 had poor outcome. Conclusions: Distraction by traction table or femoral distractor helps us to reduce the fracture by overcoming the pull of gastrocnemius in 2 week old fracture correcting hyperextension/recurvatum deformity. This method can be used as viable alternative in minimally invasive plating causing less chance of infection preserving maximal joint movement.